Immune response to hepatitis A vaccine in patients with HIV. Issue 16 (10th April 2019) - Fritzsche, Carlos; Bergmann, Lisa; Loebermann, Micha; Glass, Aenne; Reisinger, Emil C.
Abstract: Objectives: The aim of this study was to evaluate the impact of various factors that may influence the immunologic response to hepatitis A mono-vaccine or hepatitis A/B co-vaccine (Twinrix®) in HIV-infected patients. Design: Retrospective cross-sectional study. Methods: HIV positive patients with a full course of hepatitis A vaccine were tested for HAV antibodies. The seroconversion rates were determined, and the influence of several factors including CD4 cell counts, CD4/CD8 ratio, plasma viral load, type of vaccine, and antiretroviral therapy at the time of vaccine, was evaluated. Results: After vaccination, 80.2% of the patients developed anti-HAV antibodies, 81.5% in the mono-vaccine group and 79.2% in the hepatitis A/B co-vaccine group. In the mono-vaccine group, factors significantly associated with a better response to the vaccine were higher CD4 cell count, higher CD4/CD8 ratio, and shorter time interval from vaccine to serological control. In patients who received the hepatitis A/B co-vaccine, younger age and female sex were significantly associated with better vaccine response. Multivariable logistic regression analysis revealed time interval from vaccine to serological control of more than 5 years vs. less than 1 year to be significantly associated with decrease of seroconversion after HAV vaccine. Conclusions: The response to hepatitis A vaccine is impaired in HIV positive patients. HIV patients, at least those older than 30, should be tested for seroconversion after receiving the hepatitis A vaccine. As hepatitis A titers may rapidly decline, control serology during follow-up should be proposed, possibly within two years. However, vaccine type does not play a role in vaccine response.